Prevalence of musculoskeletal disorders in elderly population in a rural community of Bangladesh - Hasan, Moinul; Miah Sarker, Md. Zilan; Ahmed, Md. Shamim; Islam, Md. Tanvir (International Journal of Research in Medical Sciences, 2023)
Background: Musculoskeletal disorders are a leading source of physical impairment in elderly, and the frequency of these disorders is anticipated to increase rapidly as the population ages. In Bangladesh, musculoskeletal disorders among the elderly are on the rise, causing them immense misery. The aim of this study to find out prevalence of musculoskeletal disorder in this age group in a rural community of Bangladesh. Methods: A descriptive cross-sectional study was conducted over the period of one year from April 2017 to March 2018 in a few villages of Mokshedpur union of Dohar Upazila in Dhaka district of individuals with 60 and above. Modified COPCORD (Community Oriented Program for Control of Rheumatic Disorders) questionnaire was used to detect positive respondents. Results: The prevalence of musculoskeletal pain was 52.10%. Prevalence was higher in women, 113 (56.6%) than men, 85 (43.4%). Most of the patient belongs to age group 60-69 (79.3%). Higher prevalence rates were observed in housewife (42%), retired person (24%) and cultivators (17%). Most of the individual had no smoking habit, 145 (73.2) and 42.9% are daily smokeless tobacco users. Lower back pain (42.4%) and knee pain (37.4%) were prevalent among the study group. Non-specific low back pain (28.8%) and osteoarthritis in the knee (26.3%) were prevalent among the study group. Among all the disorder, female is prevalent than male. Conclusions: Musculoskeletal disorders are common causes of morbidity and disability in rural communities of Bangladesh. Women are affected more frequently than men. Mechanical disorders are more common than inflammatory arthropathies.